Efektivitas Program Bolsa da Mãe-Jerasaun Foun (BdM-JF) di kantor Ministerio Solidariedade Sosial no Inkluzaun (MSSI) Timor-Leste. - Salvador Suro Dos Santos Bucar; Putu Eka Purnamaningsih; I Putu Dharmanu Yudartha (CV. Lenggogeni Data Publishing, 2024)
The main objective of the Bolsa da Mae Jerasaun Foun Program (New Generation Scholarship Program) is to reduce poverty, reduce malnutrition and food shortages as well as strengthen the household economy, and improve the quality of Human Resources (HR), especially in poor community groups. The informants for this research consisted of 1) the Social Security Institute, 2) the main director of Social Solidarity, 3) pregnant women who were recipients of the Bolsa da Mãe program. Data collection techniques were carried out by conducting interviews and observations. The data analysis technique used was qualitative research with a descriptive approach. The results of this research indicate that the implementation of the Bolsa da Mae Jerasaun Foun Program (New Generation Scholarship recipients) has been running well. The Bolsa da Mae Jerasaun Foun (New Generation Scholarship recipients) program can run effectively and can help eradicate existing poverty. This is one of the important factors that can also influence the current level of poverty. The Bolsa da Mae Jerasaun Foun program (New Generation Scholarship recipients) is rightly targeted at recipients who really need it. Abstrak Tujuan utama dari Program Bolsa da Mae Jerasaun Foun (Program beasiswa generasi baru) adalah untuk mengurangi kemiskinan, pengurangan kekurangan gizi dan kekurangan pangan serta penguatan ekonomi rumah tangga, dan meningkatkan kualitas Sumber Daya Manusia (SDM) terutama pada kelompok masyarakat miskin. Informan penelitian ini terdiri dari 1) Lembaga Jaminan Sosial, 2) Direktur utama Solidaritas Sosial, 3) Ibu hamil penerima progam Bolsa da Mãe. Teknik pengumpulan data dilakukan dengan melakukan wawancara dan observasi. Teknik analisis data yang dilakukan adalah penelitian kualitatif dengan pendekatan deskriptif. Hasil penelitian ini menunjukkan bahwa pelaksanaan program Efektivitas Program Bolsa da Mae Jerasaun Foun (penerima Beasiswa Generasi Baru sudah berjalan dengan baik. program Bolsa da Mae Jerasaun Foun (penerima Beasiswa Generasi Baru) dapat berjalan dengan efektif maka dapat membantu dalam memberantas kemiskinan yang ada. Ini merupakan salah satu faktor penting yang juga dapat mempengaruhi tingkat kemiskinan yang ada saat ini. Dari program Bolsa da Mae Jerasaun Foun (penerima Beasiswa Generasi Baru) sudah tepat sasaran kepada penerima yang benar-benar membutuhkan. Kata Kunci: Efektivitas, Program Bolsa Da Mae Jerasaun Foun